How do you prove #(1 + tan^2x)/(1-tan^2x) = 1/(cos^2x - sin^2x)#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

4
Bdub Share
Mar 8, 2018

Answer:

See Below

Explanation:

#LHS: (1+tan^2x)/(1-tan^2x)#

#=(1+sin^2x/cos^2x)/(1-sin^2x/cos^2x)#

#=((cos^2x+sin^2x)/cos^2x)/((cos^2x-sin^2x)/cos^2x)#

#=(cos^2x+sin^2x)/cancel(cos^2x) *cancel(cos^2x)/(cos^2x-sin^2x) #

#=(cos^2x+sin^2x)/(cos^2x-sin^2x)#

#=1/(cos^2x-sin^2x)#

#=RHS#

Was this helpful? Let the contributor know!
1500
Impact of this question
8899 views around the world
You can reuse this answer
Creative Commons License